Carbon dioxide reduction photocatalyst particle and production method thereof

JP2025022681APending Publication Date: 2025-02-14SUMITOMO METAL MINING CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023210982
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-01
Filing Date
2023-12-14
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、CO選択率を高いレベルに維持しながら大きいCOガス生成速度を示す二酸化炭素還元光触媒粒子及びその製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022681000001_ABST
    Figure 2025022681000001_ABST
Patent Text Reader

Abstract

To provide: a carbon dioxide reduction photocatalyst particle exhibiting a large carbon monoxide gas generation rate while maintaining a high level of a carbon monoxide selection rate; and a production method thereof.SOLUTION: A carbon dioxide reduction photocatalyst particle includes a base material particle and metal silver (Ag) particles supported on a surface of the base material particle. Therein the base material particle contains one or more selected from a group consisting of tantalum oxide (Ta2O5), sodium tantalate (NaTaO3), and zinc tantalate (ZnTa2O6), and shows a peak A located in a wavelength range of 200 nm to 300 nm and a peak B located in a wavelength range of 480 nm to 530 nm in a diffuse reflectance spectrum, with a ratio (IB / IA) of intensity of peak B (IB) to intensity of peak A (IA) being 50% or less.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to carbon dioxide reducing photocatalyst particles and a method for producing the same. [Background technology]

[0002] Water splitting and carbon dioxide reduction technology using semiconductor photocatalyst particles is attracting attention as a technology that can solve energy and environmental problems. By supporting particles made of silver (Ag) or other materials as co-catalysts on these photocatalyst particles, it is expected that the effect of trapping electrons generated by photoexcitation and promoting charge separation and the effect of selecting carbon dioxide reduction products can be achieved. For example, with a normal photocatalyst, water is split into hydrogen (H2) and oxygen (O2) when irradiated with light. In contrast, with a photocatalyst supporting silver (Ag) particles, carbon monoxide (CO) is produced along with hydrogen (H2) through the reduction of carbon dioxide (CO2).

[0003] Carbon monoxide (CO) is an important starting material in the chemical and industrial industries, and can be reacted with hydrogen to synthesize various fuels and chemicals. Therefore, in a carbon dioxide reduction photocatalyst, it is desirable to have a high carbon monoxide production rate, i.e., a high CO selectivity. Here, CO selectivity is the ratio of the CO gas production rate to the total of the hydrogen (H2) gas production rate (amount produced) and carbon monoxide (CO) gas production rate produced by the reduction reaction, as expressed in the following formula (1).

[0004]

number

[0005] Meanwhile, methods such as chemical reduction, impregnation, and photoelectrodeposition (photoelectrodeposition) have been conventionally known as methods for supporting metal particles such as silver (Ag). For example, Patent Document 1 describes a method for reducing carbon dioxide, which includes irradiating light to CO2, H2O, and a photocatalyst to generate CO2 by a reaction that reduces CO2, using a catalyst in which silver is supported on gallium oxide by photoelectrodeposition or impregnation, adding gallium oxide powder to an alcoholic aqueous solution containing a silver precursor such as silver nitrate and mixing it, and then irradiating light to reduce the silver precursor, and impregnation adding gallium oxide to an aqueous silver precursor solution, stirring the mixture, removing water, and then heating and drying the mixture, and then calcining the mixture in air (claims 1, 2, and

[0015] of Patent Document 1).

[0006] Although not related to carbon dioxide reduction catalysts, Patent Document 2 discloses a method for producing a precious metal nanomaterial, which comprises the steps of irradiating ultrasonic waves to disperse one or more types of precious metal oxide in a solvent to obtain a precious metal oxide dispersion, and heating the precious metal oxide dispersion (Claim 1 of Patent Document 2). It also describes that by further containing a carrier for carrying the precious metal in the solvent, it is possible to obtain a precious metal nanomaterial that is supported on the surface of the carrier with high dispersibility, and that this can be suitably used as a catalyst for fuel cells, a catalyst for material synthesis, etc. (Claim 6 and

[0014] of Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-192302 A [Patent Document 2] JP 2008-024968 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the inventors have found that the photocatalysts prepared by the impregnation method or photoelectrodeposition method proposed in Patent Document 1 have a certain effect but have room for improvement. That is, in order to fully exert the effect of the co-catalyst silver (Ag), it is desirable to increase the amount of Ag supported to a certain extent. It is also desirable to make the particle size of Ag small, on the order of several tens of nm or less. This is because catalytic activity is lost if the particle size is too large. However, in the photocatalyst particles prepared by the impregnation method or photoelectrodeposition method, there is a problem that if the amount of co-catalyst supported (Ag concentration) is increased, the Ag particles aggregate and the particle size becomes large. Therefore, it is difficult to support a large amount of Ag particles with a small particle size.

[0009] Patent Document 2 does not intend to use precious metal nanomaterials as carbon dioxide reduction photocatalysts, much less to reduce the particle size of nanomaterials to the order of several tens of nanometers. In fact, in the examples of Patent Document 2, it merely teaches that precious metal (Pt) nanoparticle-supported spherical carbon and precious metal (Pt) nanotubes are produced, and that they are suitable for use as catalysts for fuel cells, catalysts for material synthesis, medical and food additives, and conductive pastes (

[0043] to

[0062] of Patent Document 2).

[0010] On the other hand, when synthesizing metal particles, a method is known in which the raw material concentration is reduced and a large amount of organic protective agent is used to synthesize uniform and fine particles. However, when photocatalyst particles are produced using this method, there are problems in that the yield of photocatalyst particles is low and the organic protective agent adheres to the particle surface. Since the attached organic protective agent reduces the catalytic activity, the catalyst particles must be calcined at high temperatures to decompose and remove it. In catalyst particles that have been calcined in this way, the particle size of the metal particles becomes large. Therefore, it is difficult to support fine Ag particles in a high amount with high dispersion using conventional methods, and there are limitations in efficiently producing photocatalyst particles with excellent catalytic performance, especially CO selectivity.

[0011] The present inventors have conducted research in light of such conventional problems. As a result, they have found that carbon dioxide reduction photocatalyst particles having a base material particle of a predetermined composition can be provided with metal Ag particles by ultrasonic reduction, thereby obtaining carbon dioxide reduction photocatalyst particles that exhibit a diffuse reflectance spectrum with a predetermined peak intensity ratio. They have also found that the photocatalyst particles obtained by this method exhibit a high CO gas generation rate while maintaining a high level of CO selectivity.

[0012] The present invention was completed based on such findings, and an objective of the present invention is to provide carbon dioxide reduction photocatalyst particles that exhibit a high CO gas production rate while maintaining a high level of CO selectivity, and a method for producing the same. [Means for solving the problem]

[0013] The present invention encompasses the following embodiments (1) to (6). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less." In this specification, any combination of suitable embodiments can be adopted as long as technical consistency can be achieved. For example, one of the suitable numerical ranges can be combined with the other.

[0014] (1) A composition comprising base particles and metallic silver (Ag) particles supported on the surfaces of the base particles, The base particles include one or more selected from the group consisting of tantalum oxide (Ta2O5), sodium tantalate (NaTaO3), and zinc tantalate (ZnTa2O6); In the diffuse reflectance spectrum, a peak A is located in the wavelength region of 200 nm or more and 300 nm or less, and a peak B is located in the wavelength region of 480 nm or more and 530 nm or less, and the intensity of the peak A (I A ) with respect to the intensity of peak B (I B ) ratio (I B / I A ) is 50% or less.

[0015] (2) The carbon dioxide reducing photocatalyst particles according to (1) above, in which the amount of the metallic silver (Ag) particles supported is greater than 0 mass % and less than 1.0 mass % relative to the base particles.

[0016] (3) The carbon dioxide reducing photocatalyst particles according to (1) or (2) above, wherein the particle size of the metallic silver (Ag) particles is 0.1 nm or more and 5 nm or less.

[0017] (4) A carbon dioxide reduction photocatalyst particle according to any one of (1) to (3) above, which has a CO selectivity of 50% or more in a CO2 reduction photoreduction catalyst performance evaluation test.

[0018] (5) A method for producing carbon dioxide reducing photocatalyst particles comprising base particles and metallic silver (Ag) particles supported on the surfaces of the base particles, comprising: A step of adding base particles and a silver (Ag) source to a reduction solution to prepare a reaction solution; and The method includes a step of irradiating the reaction liquid with ultrasonic waves to prepare base particles carrying metallic silver (Ag) particles, The method, wherein the base particles include one or more selected from the group consisting of tantalum oxide (Ta2O5), sodium tantalate (NaTaO3), and zinc tantalate (ZnTa2O6).

[0019] (6) The method according to (5) above, wherein the amount of the metallic silver (Ag) particles supported is more than 0 mass% and less than 1.0 mass% with respect to the base particles. Effect of the Invention

[0020] According to the present invention, there are provided carbon dioxide reduction photocatalyst particles that exhibit a high CO gas production rate while maintaining a high level of CO selectivity, and a method for producing the same. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of an evaluation device. [Diagram 2] The mechanism of photocatalytic reaction is shown. [Diagram 3] The mechanism of Ag particle support by ultrasonic reduction method is shown. [Figure 4] 1 shows X-ray absorption spectra of photocatalyst particles (examples C-1 to C-4, etc.). [Figure 5A] The TEM image of the photocatalyst particles (example C-1) is shown. [Figure 5B] The TEM image of the photocatalyst particles (example C-2) is shown. [Figure 5C] The TEM image of the photocatalyst particles (Example C-3) is shown. [Figure 5D] The TEM image of the photocatalyst particles (Example C-4) is shown. [Figure 6] 1 shows the diffuse reflectance spectra of photocatalyst particles (Examples A-1 to A-3, etc.). [Figure 7] 1 shows the diffuse reflectance spectra of photocatalyst particles (Examples B-1 to B-2, etc.). [Figure 8] The diffuse reflectance spectra of photocatalyst particles (examples C-1 to C-4, etc.) are shown. [Figure 9] 1 shows the diffuse reflectance spectra of photocatalyst particles (Examples D-1 to D-3 and D-7). [Figure 10] Diffuse reflectance spectra of photocatalyst particles (Examples D-4 to D-6) are shown. [Figure 11] The CO2 reduction photocatalytic performance of photocatalyst particles (Examples A-1 to A-3) is shown. [Figure 12] The CO2 reduction photocatalytic performance of photocatalyst particles (Examples B-1 to B-2) is shown. [Figure 13] The CO2 reduction photocatalytic performance of photocatalyst particles (examples C-1 to C-4) is shown. [Figure 14] The CO2 reduction photocatalytic performance of photocatalyst particles (Examples D-1 to D-7) is shown. [Figure 15] An atomic resolution TEM image of a photocatalyst particle (Example D-3) is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] A specific embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described below. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.

[0023] <<1. Carbon dioxide reduction photocatalyst particles>> The carbon dioxide reduction photocatalyst particles of this embodiment (hereinafter sometimes simply referred to as "photocatalyst particles") contain base particles and metallic silver (Ag) particles supported on the surfaces of these base particles. The base particles contain one or more selected from the group consisting of tantalum oxide (Ta2O5), sodium tantalate (NaTaO3), and zinc tantalate (ZnTa2O6). Furthermore, the carbon dioxide reduction photocatalyst particles have, in their diffuse reflectance spectrum, peak A located in a wavelength range of 200 nm or more and 300 nm or less, and peak B located in a wavelength range of 480 nm or more and 530 nm or less. The intensity of peak A (I A ) versus the intensity of peak B (I B ) ratio (I B / I A ) is less than 50%.

[0024] The base material particles function as a main catalyst. The base material particles contain one or more main components selected from the group consisting of tantalum oxide (Ta2O5), sodium tantalate (NaTaO3), and zinc tantalate (ZnTa2O6). Here, the main component refers to a component that occupies 50 mass% of the base material particles. By using tantalum oxide, sodium tantalate, and / or zinc tantalate as the main component, photocatalyst particles that exhibit excellent catalytic performance can be obtained. The ratio of the main component in the base material particles is preferably large. The ratio of the main component may be 60 mass% or more, 70 mass% or more, 80 mass% or more, or 90 mass% or more.

[0025] The metallic Ag particles function as a co-catalyst, and their particle size is on the order of nm or less. The particle size of the metallic Ag particles is preferably 0.1 nm or more and 5 nm or less, and more preferably 1 nm or more and 5 nm or less. By supporting such fine Ag particles, the catalytic performance of the photocatalyst particles is improved. This is because the number of surface active points of the base particles increases by supporting a fine co-catalyst. The particle size of the metallic Ag particles can be determined by TEM observation.

[0026] The photocatalyst particles of this embodiment have a peak A located in the wavelength region of 200 nm to 300 nm and a peak B located in the wavelength region of 480 nm to 530 nm in the diffuse reflectance spectrum. A ) versus the intensity of peak B (I B ) ratio (I B / I A The peak intensity ratio (I B / I A By controlling the peak intensity ratio (I B / I A ) is preferably 40% or less, more preferably 30% or less, even more preferably 20% or less, particularly preferably 10% or less, and most preferably 5% or less. On the other hand, in order to fully exert the function of the promoter (Ag particles), B / I A It is desirable that the peak intensity ratio (I B / I A ) is preferably 0.5% or more, more preferably 1% or more, and even more preferably 2% or more.

[0027] It is sufficient that at least one peak exists in each of the wavelength ranges of 200 nm to 300 nm and 480 nm to 530 nm. For example, when multiple peaks exist in the wavelength range of 480 nm to 530 nm, the intensity ratio (I B / I A ) should be within a specified range (50% or less).

[0028] A diffuse reflectance spectrum is an absorption spectrum obtained by the diffuse reflectance method. When light is irradiated onto a solid sample such as a powder, some of the light leaves the sample after a scattering process. In the scattering process, part of the irradiated light is reflected by the surface of the sample, and the rest enters the sample. Of the incident light that enters, part is absorbed by the electronic transition state of the sample, and the rest leaves the sample. An absorption spectrum can be obtained from the incident light intensity of ultraviolet or visible light and the light intensity after the scattering process.

[0029] In the photocatalyst particles of this embodiment, the amount (Ag concentration) of the promoter (Ag particles) is preferably more than 0 mass% and less than 1.0 mass% with respect to the base material particles. By increasing the amount of support to a certain extent, the effect of the promoter can be fully exhibited. Therefore, when the photocatalyst is used for CO2 reduction, it is possible to significantly increase the CO gas generation rate and CO selectivity. On the other hand, by appropriately suppressing the amount of support, it is possible to suppress a decrease in the CO gas generation rate. The amount of support can be adjusted by controlling the blending amount of the Ag source and the ultrasonic treatment conditions. The amount of support is more preferably 0.1 mass% or more and 0.5 mass% or less.

[0030] The photocatalyst particles of this embodiment have excellent catalytic performance, particularly CO selectivity. For example, in a CO2 reduction photocatalyst performance evaluation test, the CO selectivity is 30% or more. Therefore, it is possible to increase the proportion of the amount of CO gas generated by CO2 reduction. The CO selectivity may be 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, or 90% or more. The upper limit of the CO selectivity is not particularly limited, but is typically 98% or less, more typically 95% or less.

[0031] The CO2 reduction photocatalytic performance evaluation test may be performed using a known evaluation device. An example of the evaluation device is shown in FIG. 1. The evaluation device (2) is composed of a tank (4) and a high-pressure mercury (Hg) lamp (6) installed inside the tank (4). The tank (4) is filled with an evaluation solution (22). The tank (4) is also equipped with a gas inlet pipe (8), a gas outlet pipe (10), a pH meter (12), a rubber stopper (14), and a stirrer (16). A bubbling filter (18) is installed at the tip of the gas inlet pipe (8). The mercury lamp (6) is cooled by cooling water (20) flowing around it.

[0032] The evaluation test may be performed as follows. Pure water, sodium bicarbonate (NaHCO3), and a sample (photocatalyst particles) are mixed to prepare an evaluation solution (22). This evaluation solution (22) is placed in a tank (4) of an evaluation device (2) and stirred with a stirrer (16). Carbon dioxide (CO2) gas (30) is blown in through a gas inlet pipe (8), and at the same time, UV light from a high-pressure mercury lamp (6) is irradiated onto the evaluation solution (22). After irradiation for a predetermined time, the generated gas (32) is introduced through a gas outlet pipe (10) into a gas chromatograph (34) and analyzed there. The generation rates (amounts) of hydrogen (H2), oxygen (O2), and carbon monoxide (CO) are determined by this analysis. The obtained generation rates are used to calculate the CO selectivity based on the following formula (1).

[0033]

number

[0034] The diffuse reflectance spectrum has peaks in specific wavelength ranges (200 nm to 300 nm, 480 nm to 530 nm), and the peak intensity ratio (I B / I AThe details of the mechanism by which the photocatalyst particles of this embodiment, in which the β-axis angle θ is within a predetermined range (50% or less), exhibit a high CO gas generation rate while maintaining a high CO selectivity, are unknown. However, it is speculated that the particle size of the metal Ag particles and the electronic transition state are related. In other words, the spectrum obtained by the diffuse reflectance method (diffuse reflectance spectrum) reflects the electronic transition state of the sample, such as the valence of the species, the coordination structure, and the ligand field. In addition, when the sample is a fine particle, it may show different absorption energy depending on the particle size. For example, when the metal Ag particles are fine particles, it is known that they give an absorption band in the wavelength range corresponding to plasmon resonance. Therefore, it is considered that the photocatalyst particles of this embodiment, which have a peak in a specific wavelength range, have fine and specific electronic transition states of the supported Ag particles.

[0035] On the other hand, it is expected that the particle size and electronic transition state of the Ag particles will affect the catalytic performance of the photocatalyst, for example, the CO selectivity. This will be explained based on the mechanism of CO2 reduction of photocatalyst particles carrying metal Ag particles (Figure 2). As shown in Figure 2, when light with energy hν is irradiated onto the particles, electrons (e - ) and holes (h + At this time, the metallic Ag particles (promoter) undergo charge separation (electron e - and hole h + The separation of holes (h + ) reacts with the surrounding water (HO), and the reaction shown in the following formula (2) proceeds to the right, producing oxygen (O2) and protons (H + ) and electrons (e - ) is converted into carbon dioxide (CO2) and protons (H + ), the reactions shown in the following formulas (3) and (4) proceed to the right, producing carbon monoxide (CO), water (H2O), and hydrogen (H2). In principle, the reaction shown in the following formula (5) proceeds when the reactions in the following formulas (2) to (4) are combined.

[0036]

number

number

number

number

[0037] When the reactions of the above formulas (3) and (4) occur to the same extent, the CO selectivity (CO generation rate / (H2 generation rate+CO generation rate)) is constant as shown in the above formula (5). However, in reality, these reactions do not necessarily occur to the same extent. When the reaction of the above formula (3) occurs preferentially, the CO selectivity increases.

[0038] It has been reported that in the reaction of formula (3) above, carbon dioxide (CO2) is adsorbed on the catalyst surface as carbonate species, and when irradiated with light, it changes to a formate species, which is a reaction intermediate, and then interacts with water molecules to become carbon monoxide (CO). This report also suggests that the Ag promoter promotes the generation of reaction intermediates. Therefore, by enhancing the effect of charge separation and the effect of generating reaction intermediates by metal Ag particles (promoter), it is expected that the reaction of formula (3) above will occur preferentially, and the CO selectivity will be further improved.

[0039] In this regard, as described later, the photocatalyst particles of this embodiment are supported with the co-catalyst (Ag particles) by ultrasonic reduction. The diffuse reflectance spectrum has a peak in a specific wavelength range, and the peak intensity ratio is within a predetermined range. In such photocatalyst particles, it is presumed that the supported Ag particles are present on the surface of the base material particles in the form of clusters so fine (Å order) that they cannot be observed with a transmission electron microscope (TEM). It is also considered that a unique electronic transition state is created by hot spots and radicals generated during ultrasonic treatment. By supporting cluster-like ultrafine Ag particles having a unique electronic transition state, the number of CO2 reduction sites of the photocatalyst particles becomes larger than when they are supported by other methods, and this is thought to lead to an improvement in catalytic activity, especially the CO generation rate.

[0040] <<2. Method of manufacturing photocatalyst particles>> The method for producing the photocatalyst of this embodiment includes the following steps: a step of adding base particles and a silver (Ag) supply source to a reducing solution to prepare a reaction solution (mixing step), and a step of irradiating the reaction solution with ultrasonic waves to prepare base particles carrying metallic silver (Ag) particles (ultrasonic treatment step). The base particles include one or more selected from the group consisting of tantalum oxide (Ta2O5), sodium tantalate (NaTaO3), and zinc tantalate (ZnTa2O6). Details of each step are described below.

[0041] <Mixing process> In the mixing step, the base material particles and a silver (Ag) source are added to the reducing solution to prepare a reaction solution. The base material particles may be commercially available products or may be crushed to use them as is. Alternatively, they may be synthesized. For example, sodium tantalate (NaTaO3) can be synthesized by firing a mixture of sodium carbonate (Na2CO3) and tantalum oxide (Ta2O5). Zinc tantalate (ZnTa2O6) can be synthesized by firing a mixture of zinc oxide (ZnO) and tantalum oxide (Ta2O5). The synthesized base material particles may be crushed.

[0042] The size of the particles is not particularly limited. For example, the average particle diameter of the particles is 0.3 to 5.0 μm. Furthermore, the shape of the particles is not particularly limited. For example, it may be spherical, irregular, or anisotropic (rod or plate-like). When the particles are rod-like, for example, those with a major axis diameter of 1.0 to 5.0 μm and a minor axis diameter of 0.3 to 1.0 μm can be used.

[0043] The silver (Ag) supply source is not limited as long as it can supply silver (Ag). Specific examples include oxides, inorganic metal salts, and / or organic metal compounds. Examples of inorganic metal salts include nitrates, chlorides, and / or sulfates. The Ag supply source may be soluble in the reducing solution, or may not be soluble in the reducing solution. A suitable Ag supply source includes silver oxide. Silver oxide is composed only of silver ions and oxygen ions, so it is easy to handle and does not have problems such as waste disposal. As silver oxide, Ag2O, AgO, and Ag2O3, which have different oxidation numbers of silver, are known, and any of them can be used. However, Ag2O, which is more easily available, is preferable. The size of the Ag supply source is also not particularly limited. For example, the average particle size of the Ag supply source is 0.3 to 3.0 μm.

[0044] The mixing ratio of the base particles and the Ag supply source can be adjusted so that the amount of co-catalyst (Ag particles) supported in the final photocatalyst particles is the desired value. If the amount of co-catalyst supported is too small, it becomes difficult to fully utilize the effect of the co-catalyst. Therefore, when the photocatalyst particles are used for CO2 reduction, the CO gas generation rate and CO selectivity are low. On the other hand, if the amount of co-catalyst supported is too large, the CO gas generation rate decreases.

[0045] The reducing liquid is not limited as long as it is a liquid having reducing properties. It may be a liquid having reducing properties by itself, or may be a liquid having no reducing properties in which a reducing agent is dissolved. However, it is preferable that the reducing liquid is a liquid having reducing properties by itself. It is also not necessary to contain a separate reducing agent. As such a reducing liquid, alcohols such as ethanol and propanol, which are less toxic and easily available, are preferable. A mixed liquid of alcohols and water can also be used. However, when using a mixed liquid, if the water content is excessively high, it becomes difficult to exert a sufficient reducing effect. Therefore, the water content in the reducing liquid is preferably 50% by volume or less, more preferably 25% by volume or less. The lower limit of the water content is not particularly limited, and may be 0% by volume.

[0046] <Ultrasonic treatment process> In the ultrasonic treatment process, ultrasonic waves are applied to the reaction solution to produce base particles carrying metallic Ag particles. At this time, the surface of the Ag supply source in the reaction solution is ultrasonically reduced to become metallic Ag particles, which are then carried on the surface of the base particles. The base particles carrying metallic Ag particles can be used as photocatalyst particles.

[0047] The mechanism of metallic Ag particle support is explained using Figure 3. When ultrasonic waves are irradiated, compression waves are generated in the reaction solution, which generates repeated positive and negative pressures. During negative pressure cycles, countless fine bubbles are generated in the reaction solution due to evaporation. During positive pressure cycles, these bubbles collapse and give a strong impact force to the surroundings. This phenomenon is called ultrasonic cavitation. Cavitation uniformly disperses the base material particles and Ag source in the reaction solution, and cleans the surface. Cavitation also generates tiny hot spots of high temperature and pressure. The generated hot spots decompose and reduce the Ag source, and act on the reaction solution to generate radicals, which promote the decomposition and reduction of the Ag source. In this way, metallic Ag particles are generated from the Ag source.

[0048] For example, when solid silver oxide (Ag2O) is used as the Ag supply source, hot spots and radicals act on Ag2O, causing Ag2O to decompose and reduce on the surface, resulting in the precipitation of Ag particles. These Ag particles grow gradually, and when they grow to a certain extent, the interfacial stress between Ag2O and the Ag particles becomes a limit and they are detached. Alternatively, an intermediate product is generated from Ag2O by the action of ultrasound, and hot spots and radicals act on this intermediate product to generate Ag particles in the reaction solution. The detached or generated Ag particles move to the surface of the base material particles by the physical action of ultrasound and are adsorbed there. In this way, base material particles carrying Ag particles are obtained. The Ag particles generated by ultrasonic reduction are fine. In addition, since no organic protective agent or high-temperature firing is required, it is possible to produce base material particles (photocatalyst particles) carrying Ag particles in a fine state.

[0049] If the photocatalyst particles contain an Ag source other than Ag particles, it may be difficult to fully exert the effect of the co-catalyst. In this regard, by using ultrasonic treatment, it is possible to obtain photocatalyst particles that contain almost no Ag source (silver oxide, etc.). For example, it is possible to obtain photocatalyst particles in which no peak of silver oxide (Ag2O) is observed in the X-ray diffraction pattern.

[0050] There is no need to use a special device for the ultrasonic treatment, and a device equipped with a normal ultrasonic oscillation source may be used. For example, a commercially available ultrasonic cleaner may be used. The treatment may be performed under normal conditions. For example, the frequency of the ultrasonic waves may be 20 to 100 kHz, or 28 to 45 kHz. The ultrasonic treatment may be performed continuously at the same frequency, or the frequency may be switched during the treatment using a frequency oscillation switching mode. The frequency may be switched once, or multiple times. By performing the treatment in a frequency oscillation switching mode (for example, a two-frequency switching oscillation mode of 28 kHz / 45 kHz), it is possible to further improve the dispersibility of the base material particles in the liquid. In addition, the output of the ultrasonic waves may be 10 to 500 W, or 50 to 200 W. Furthermore, the treatment time may be 1 to 10 hours. By extending the treatment time, it is possible to convert all of the Ag supply source into Ag particles and support them on the base material particles. On the other hand, by shortening the treatment time, it is possible to adjust the amount of the co-catalyst (Ag particles) supported. The treatment time is preferably 2 hours or more and 10 hours or less.

[0051] The product obtained by ultrasonic treatment (base material particles carrying Ag particles) exists in a dispersed or precipitated state in the reaction liquid. Therefore, the product is recovered from the reaction liquid and then dried. The recovery can be performed using a known separation method such as filtration or centrifugation. Drying can be performed under conditions that do not cause excessive grain growth of the Ag particles, for example, at 100°C or less.

[0052] The amount of the co-catalyst (Ag particles) carried in the final photocatalyst particles can be adjusted by controlling the amount of the Ag source and the ultrasonic treatment conditions. The amount of the metal Ag particles carried is preferably more than 0% by mass and less than 1.0% by mass, more preferably 0.1% by mass or more and 0.5% by mass or less, based on the base material particles.

[0053] <Heat treatment process> If necessary, the base material particles carrying the metallic Ag particles may be subjected to a heat treatment. By subjecting the Ag-loaded base material particles prepared by the ultrasonic loading method to a heat treatment, organic matter remaining on the particle surface, such as organic matter derived from ethanol, can be removed, and the particle size of the Ag particles can be reduced. This heat treatment effect allows the more selective generation of CO when used as a CO2 reduction photocatalyst.

[0054] The heat treatment is preferably carried out at 100°C or higher in an oxygen-containing atmosphere. There is no need to use a special device for the heat treatment, and a general electric furnace capable of firing in the air can be used. At temperatures below 100°C, the effect on the decomposition of organic matter and the particle size of Ag particles is small, and the effect cannot be expected. However, the photocatalyst particles of this embodiment are not limited to those that have been subjected to heat treatment. Photocatalyst particles with sufficiently high catalytic activity can be obtained without performing heat treatment.

[0055] In this manner, photocatalyst particles consisting of base material particles carrying metallic Ag particles can be obtained.

[0056] By adopting such a manufacturing method, it is possible to easily obtain catalyst particles with excellent catalytic performance, especially CO selectivity. Although the detailed reason is unclear, it is speculated that the supported Ag particles generated by ultrasonic reduction are fine and have a unique electronic transition state. In other words, it is considered that most of the silver (Ag) generated by ultrasonic reduction treatment is in the form of ultrafine (Å order) clusters that cannot be observed by TEM. It is also considered that the unique electronic transition state is caused by the action of high-temperature and high-pressure hot spots and radicals generated during ultrasonic treatment. In fact, it has been reported that the hot spots generated by ultrasonic treatment are as high as nearly 5000°C, and it is easy to predict that the electronic transition state will change if such a high-temperature hot spot acts even for an instant. It is speculated that the fine particle size and the unique electronic transition state work together to improve catalytic performance such as CO production rate and CO selectivity.

[0057] Furthermore, according to this production method, it is possible to use a compound such as silver oxide, which is not soluble in the reaction solution, as the Ag supply source in a solid state, although this is not limited thereto. When a compound that is not soluble in the reaction solution is used, the reaction solution does not contain harmful substances such as anions, and waste liquid treatment is easy.

[0058] In contrast, other methods such as chemical reduction, impregnation, and photoelectrodeposition do not promote the generation of ultrafine clusters. In addition, hot spots are not generated during loading, and the resulting changes in the electronic transition state do not occur, which is thought to limit the improvement of catalytic performance. In addition, the impregnation and photoelectrodeposition methods require the use of a precursor solution such as an aqueous solution in which silver nitrate is dissolved. Anions such as nitrate ions contained in such precursor solutions are harmful substances that cause air pollution. Therefore, the impregnation and photoelectrodeposition methods require wastewater treatment to detoxify the harmful substances.

[0059] However, the manufacturing method of this embodiment does not exclude the use of a compound that dissolves in the reaction solution. Even in such a case, the effect of precipitating metal Ag particles with high dispersion and high loading rate can be obtained. EXAMPLES

[0060] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.

[0061] [Experimental Example A] In Experimental Example A (Examples A-1 to A-3), tantalum oxide (Ta2O5) particles were used as base particles, and Ag particles as a co-catalyst were supported on the particles to produce photocatalyst particles. The co-catalyst was supported by ultrasonic reduction, chemical reduction, or impregnation. The amount of the co-catalyst (Ag particles) supported on the base particles (Ag concentration) was fixed at 0.5 mass%.

[0062] [Example A-1] In Example A-1, Ag particles were reduced and supported by ultrasonic reduction. Specifically, photocatalyst particles were prepared by the following procedure.

[0063] First, tantalum oxide (Ta2O5, Kojundo Chemical Laboratory Co., Ltd.) particles and silver oxide (Ag2O, Fujifilm Wako Pure Chemical Co., Ltd.) particles were prepared. Next, 1.2 g of Ta2O5 particles and 6.5 mg of Ag2O particles were added to 50 mL of reducing solution to prepare a reaction solution. Ethanol (Fujifilm Wako Pure Chemical Co., Ltd.) was used as the reducing solution.

[0064] The resulting reaction solution was placed in an ultrasonic device (Honda Electronics Co., Ltd., WT-100-M) and subjected to ultrasonic treatment. The ultrasonic treatment was performed under the conditions of a two-frequency switching oscillation of 28 kHz and 45 kHz and an output of 100 W. The treatment time was 3 hours. During this time, the temperature of the reaction solution was maintained at 40°C. Through this treatment, Ag2O in the reaction solution was reduced and changed to metallic Ag. The product generated by the treatment was filtered, washed with ethanol (10 mL), and dried in air at 60°C for 1 hour, obtaining Ta2O5 particles carrying metallic Ag particles as photocatalyst particles.

[0065] [Example A-2] In Example A-2, Ag particles were reduced and supported by a chemical reduction method. Specifically, photocatalyst particles were prepared by the following procedure.

[0066] First, tantalum oxide (Ta2O5, High Purity Chemical Laboratory Co., Ltd.) particles, 0.1M silver nitrate aqueous solution (0.1MAgNO3aq, Fujifilm Wako Pure Chemical Co., Ltd.), and sodium phosphinate monohydrate (NaPH2O2·H2O, Fujifilm Wako Pure Chemical Co., Ltd.) were prepared. Sodium phosphinate monohydrate was mixed with ultrapure water to prepare a 0.4M sodium phosphinate aqueous solution.

[0067] 0.75 g of the prepared tantalic acid particles were added to 50 mL of ultrapure water, and the resulting mixture was maintained at 80°C using a water bath. Next, 0.35 mL of a silver nitrate aqueous solution (0.1 M) and 0.75 mL of a sodium phosphinate aqueous solution (0.4 M) as a reducing agent were added to the mixture, and the mixture was stirred at 80°C for 1 hour and 30 minutes to induce a chemical reduction reaction. The solution after the chemical reduction was filtered, and the resulting powder was collected. The collected powder was dried at room temperature to obtain photocatalyst particles.

[0068] [Example A-3] In Example A-3, Ag particles were reduced and supported by the conventional impregnation method. Specifically, the photocatalyst particles were prepared by the following procedure.

[0069] First, 20 mL of ultrapure water was mixed with 1.2 g of tantalum oxide (Ta2O5) particles, and the resulting mixture was maintained at 80°C using a water bath. Next, 0.56 mL of a silver nitrate aqueous solution (0.1 M) was added and stirred at 80°C for 1 hour. The heated mixture was then dried in air at 80°C for 3 hours, and the resulting dried product was calcined at 450°C for 2 hours to obtain photocatalyst particles.

[0070] [Experimental Example B] In Experimental Example B (Examples B-1 to B-2), sodium tantalate (NaTaO3) particles were used as base particles, and Ag particles were supported on the base particles to produce photocatalyst particles. The support of the co-catalyst was performed by ultrasonic reduction or chemical reduction. The amount of the co-catalyst (Ag particles) supported on the base particles (Ag concentration) was fixed at 0.5 mass%.

[0071] [Example B-1] In Example B-1, Ag particles were reduced and supported by ultrasonic reduction. Specifically, photocatalyst particles were prepared by the following procedure.

[0072] First, sodium tantalate (NaTaO3) particles were synthesized as the base particles. Specifically, 1.06g of sodium carbonate (Na2CO3) and 4.42g of tantalum oxide (Ta2O5) were mixed in an alumina mortar for 10 minutes. The resulting mixture was fired at 1150°C for 20 hours in an air atmosphere. The product obtained by firing was sized using a 100-mesh sieve to obtain NaTaO3 particles.

[0073] The obtained NaTaO3 particles were used as base particles, and the Ag particles were reduced and supported by ultrasonic reduction in the same manner as in Example A-1.

[0074] [Example B-2] In Example B-2, Ag particles were reduced and supported by chemical reduction. The synthesis of NaTaO3 particles was performed in the same manner as in Example B-1. The reduction and support were performed in the same manner as in Example A-2.

[0075] [Experimental Example C] In Experimental Example C (Examples C-1 to C-4), zinc tantalate (ZnTa2O6) particles were used as base particles, and photocatalyst particles were prepared by supporting Ag particles as a co-catalyst. The co-catalyst was supported by ultrasonic reduction, chemical reduction, impregnation, or photoelectrodeposition. The amount of the co-catalyst (Ag particles) supported relative to the base particles (Ag concentration) was fixed at 0.5 mass%.

[0076] [Example C-1] In Example C-1, Ag particles were reduced and supported by ultrasonic reduction. Specifically, photocatalyst particles were prepared by the following procedure.

[0077] First, zinc tantalate (ZnTa2O6) particles were synthesized as the base particles. Specifically, 0.814g of zinc oxide (ZnO), 4.42g of tantalum oxide (Ta2O5), and 5mL of ultrapure water were placed in an alumina mortar and mixed for 10 minutes. The resulting mixture was filtered to recover the solids, which were then dried overnight at 80°C and then fired at 1000°C for 50 hours in an air atmosphere. The product obtained by firing was sized using a 100-mesh sieve to obtain ZnTa2O6 particles.

[0078] The obtained ZnTa2O6 particles were used as base particles, and the Ag particles were reduced and supported by ultrasonic reduction in the same manner as in Example A-1.

[0079] [Example C-2] In Example C-2, Ag particles were reduced and supported by chemical reduction. ZnTa2O6 particles were synthesized in the same manner as in Example C-1. The reduction and support were performed in the same manner as in Example A-2.

[0080] [Example C-3] In Example C-3, Ag particles were reduced and supported by the impregnation method. ZnTa2O6 particles were synthesized in the same manner as in Example C-1. The reduction and support were performed in the same manner as in Example A-3.

[0081] [Example C-4] In Example C-4, Ag particles were reduced and supported by photoelectrodeposition. ZnTa2O6 particles were synthesized using the same procedure as in Example C-1. In addition, photocatalyst particles were produced by reducing silver nanoparticles using the conventional photoelectrodeposition method. Specifically, the photocatalyst particles were produced using the following procedure.

[0082] First, 1 L of ultrapure water, 1.2 g of zinc tantalate, and 0.56 mL of an aqueous silver nitrate solution (0.1 M) were mixed, and argon (Ar) gas was blown into the resulting mixed solution to replace the gas. Next, while blowing in argon gas at a flow rate of 30 mL / min, the solution was irradiated with UV light from a 400 W high-pressure Hg lamp for 3 hours to reduce the silver (Ag) ions. After the light irradiation, the solution was filtered and the powder was collected. The collected powder was dried at room temperature to obtain photocatalyst particles. The silver concentration relative to the zinc tantalate was 0.5 mass%.

[0083] [Experimental Example D] In Experimental Example D (Examples D-1 to D-7), zinc tantalate (ZnTa2O6) particles were used as the base material particles, and photocatalyst particles were produced by supporting Ag particles as a co-catalyst. The Ag particles were supported by ultrasonic reduction. The amount of the co-catalyst (Ag particles) supported on the base material particles (Ag concentration) was changed from 0 to 5.0 mass%.

[0084] [Example D-1] In Example D-1, the amount of Ag particles supported was changed to 0.1 mass %, and otherwise photocatalyst particles were produced in the same manner as in Example C-1.

[0085] [Example D-2] In Example D-2, the amount of Ag particles supported was changed to 0.25 mass %, and otherwise photocatalyst particles were produced in the same manner as in Example D-1.

[0086] [Example D-3] In Example D-3, the amount of Ag particles supported was changed to 0.5 mass %, and otherwise photocatalyst particles were produced in the same manner as in Example D-1.

[0087] [Example D-4] In Example D-4, the amount of Ag particles supported was changed to 1.0 mass %, and otherwise photocatalyst particles were produced in the same manner as in Example D-1.

[0088] [Example D-5] In Example D-5, the amount of Ag particles supported was changed to 3.0 mass %, and otherwise photocatalyst particles were produced in the same manner as in Example D-1.

[0089] [Example D-6] In Example D-6, the loading amount of Ag particles was changed to 5.0 mass%. Photocatalytic particles were prepared in the same manner as in Example D-1 except for this change.

[0090] [Example D-7] In Example D-7, the loading amount of Ag particles was changed to 0 mass%, that is, no Ag particles were loaded. Photocatalytic particles were prepared in the same manner as in Example D-1 except for this change.

[0091] (2) Evaluation of photocatalytic particles Regarding the photocatalytic particle samples obtained in Examples A-1 to D-7, evaluations of various properties were conducted as follows.

[0092] [X-ray absorption spectroscopy] Measurements of spectra at the Ag-K edge were performed using the transmission method and the fluorescence method at beamline BL14B02 in the large synchrotron radiation facility SPring-8.

[0093] [STEM observation] The samples were observed using a scanning transmission electron microscope (STEM; Hitachi High-Technologies Corporation, HD2700). The observations were made with a transmission electron image under the condition of an acceleration voltage of 200 kV. Also, the average particle diameter of the Ag particles supported on the base particles was determined as follows. That is, the particle diameters of 100 or more particles were measured from the STEM image, and the average value was taken as the average particle diameter.

[0094] [Atomic resolution TEM] Transmission electron microscope observations at the atomic resolution level were performed using a spherical aberration corrected transmission electron microscope (JEOL Ltd., JEM-2200FS). Specifically, observations were made under the condition of an acceleration voltage of 200 kV to obtain a transmission electron image.

[0095] [Diffuse reflection spectrum] Diffuse reflection spectra in the solid state were measured using an ultraviolet-visible near-infrared spectrophotometer (JASCO, V-650). The measurements were made with a bandwidth of 1.0 nm, a measurement range of 800 to 200 nm, a data acquisition interval of 0.1 nm, and a scanning speed of 200 nm / min.-1 It was carried out under the conditions of.

[0096] <CO₂ reduction photocatalytic performance> The CO₂ reduction photocatalytic performance of the samples was evaluated using the evaluation apparatus shown in Fig. 1. First, ultrapure water (1 L), NaHCO₃ (0.1 M), and photocatalytic particles (0.5 g) were mixed to prepare an evaluation solution. Next, this evaluation solution was placed in the tank of the evaluation apparatus, and while blowing carbon dioxide (CO₂) gas at a flow rate of 30 mL / min, UV light was irradiated with a 400 W high-pressure Hg lamp. The gas generated after 1 hour of irradiation was analyzed using gas chromatography (Shimadzu Corporation, GC-8A) to determine the generation rates of H₂, O₂, and CO. Then, the CO selectivity was calculated based on the following formula (1).

[0097]

Equation

[0098] (3) Evaluation results <X-ray absorption spectroscopy> For the samples (Examples C-1 to C-4) of Experimental Example C containing zinc tantalate (ZnTa₂O₆) particles as base particles, the spectra at the Ag-K shell absorption edge are shown in Fig. 4. Also shown in Fig. 4 are the spectra of silver foil (Ag foil), silver oxide (AgO, Ag₂O), and silver nitrate (AgNO₃).

[0099] The spectra of the samples of Examples C-1 to C-4 all matched the spectrum of silver foil (Ag foil) at the absorption edge. From this, it was found that the supported cocatalyst was metallic silver (Ag) particles.

[0100] <STEM observation> TEM images of the samples of Experimental Example C (Examples C-1 to C-4) are shown in Figures 5A to 5D, respectively. In the samples (Examples C-2 to C-4) in which Ag was supported by the chemical reduction (CR) method, impregnation (IMP) method, or photoelectrodeposition (PD) method, many Ag particles with diameters of 13.2 to 40.1 nm were observed on the surface of the base material particles (Figures 5B to 5D). In contrast, in the sample (Example C-1) in which Ag was supported by the ultrasonic reduction (USR) method, Ag particles with a diameter of 14.3 nm were observed, but the number was small (Figure 5A).

[0101] The amounts of promoter (Ag particles) loaded in Examples C-1 to C-4 are the same (0.5 mass%). The sample loaded by ultrasonic reduction (Example C-1) had a small number of Ag particles. Most of the loaded Ag particles became ultrafine (Å order) clusters that could not be confirmed by TEM observation, which is thought to be why only a small number of particles were observed.

[0102] <Diffuse reflectance spectrum> The diffuse reflectance spectra of samples of Experimental Examples A to C, in which the amount of promoter (Ag particles) supported was fixed at 0.5 mass%, are shown in Figures 6 to 8, respectively. The diffuse reflectance spectra shown here are normalized based on the intensity of a peak (peak A) present in the wavelength range of 200 nm or more and 300 nm or less. Figures 6 to 8 also show the spectrum of a sample that does not support a promoter (Ag particles).

[0103] All samples of Experimental Example A, which contained tantalum oxide (Ta2O5) as the base material particles, showed a large peak (Peak A) in the wavelength range of 200 to 300 nm (Figure 6). In addition, samples carrying a promoter (Ag) showed a peak (Peak B) in the wavelength range of 300 to 600 nm, but samples without a promoter showed no significant peak. From this, it is believed that Peak B in the wavelength range of 300 to 600 nm is due to the supported Ag particles.

[0104] The samples (Examples A-2 and A-3) in which the support was performed by the chemical reduction method or the impregnation method had a relatively large peak B in the wavelength range of 300 to 600 nm, but the sample (Example A-1) in which the support was performed by the ultrasonic reduction method had a relatively small peak B. Specifically, the sample of Example A-1 had a peak B in the wavelength range of 480 nm to 530 nm, and the peak intensity was smaller than the peak intensity (wavelength range 300 to 600 nm) of Examples A-2 and A-3.

[0105] The sample of Experimental Example B, which contains sodium tantalate (NaTaO3) as the base material particles, also showed results similar to those of Experimental Example A (Figure 7). That is, the samples (Examples B-1 and B-2) carrying the co-catalyst (Ag) showed peak B in the wavelength range of 300 to 600 nm, but the samples without the co-catalyst showed no significant peak. In addition, the sample (Example B-1) carrying the co-catalyst by ultrasonic reduction showed peak B in the wavelength range of 480 nm to 530 nm, and the peak intensity was smaller than the peak intensity (wavelength range 300 to 600 nm) of the sample (Example B-2) carrying the co-catalyst by a method other than ultrasonic reduction.

[0106] The sample of Experimental Example C, which contains zinc tantalate (ZnTa2O6) as the base material particles, also showed results similar to those of Experimental Example A (Figure 7). That is, the samples (Examples C-1 to C-4) that supported the promoter (Ag) showed a peak in the wavelength range of 300 to 600 nm, but the samples that did not support the promoter did not show any significant peak. In addition, the sample (Example C-1) that was supported by the ultrasonic reduction method showed a peak (Peak B) in the wavelength range of 480 nm to 530 nm, and the peak intensity was smaller than the peak intensity (wavelength range 300 to 600 nm) of the samples (Examples C-2 to C-4) that were supported by methods other than the ultrasonic reduction method.

[0107] In consideration in conjunction with the results of STEM observation, regardless of the type of base material particles, peak B observed in the wavelength range of 300 to 600 nm in the diffuse reflectance spectrum can be said to be a peak based on Ag particles supported on the surface of the base material particles. When supported by methods other than the ultrasonic reduction method (chemical reduction method, impregnation method, photoelectrolysis method), the particle size of the supported Ag particles is relatively large, and thus it is considered that the intensity of peak B becomes relatively large. On the other hand, when supported by the ultrasonic reduction method, most of the supported Ag particles exist as ultrafine clusters, and as a result, it is considered that the intensity of peak B has become small.

[0108] Diffuse reflectance spectra of samples (Examples D-1 to D-7) of Experimental Example D in which the loading amount of the cocatalyst (Ag particles) was changed from 0 to 5.0 mass% are shown in FIGS. 9 and 10. Except for the sample (Example D-7) not supporting the cocatalyst (Ag), all samples showed peaks A and B in the wavelength range of 200 nm or more and 300 nm or less and in the wavelength range of 480 nm or more and 530 nm or less. Also, the intensity of peak B increased as the loading amount of the cocatalyst increased.

[0109] <CO2 reduction photocatalytic performance> The CO2 reduction photocatalytic performance (gas generation rate and CO selectivity) obtained for the samples of Experimental Examples A to C in which the loading amount of the cocatalyst (Ag) was fixed at 0.5 mass% is shown in Table 1 below and FIGS. 11 to 13. In Table 1 below, the peak wavelengths and intensity ratios (I B / I A ) of peak A and peak B in the diffuse reflectance spectrum are also shown.

[0110] In the sample of Experimental Example A containing tantalum oxide (Ta2O5) as the base material particles, when supported by the ultrasonic reduction method (Example A-1), the peak intensity ratio (I B / I A ) was 50% or less. Also, the CO gas generation rate was high compared to when supported by other methods (chemical reduction method, impregnation method) (Examples A-2, A-3) while maintaining a CO selectivity of 80% or more.

[0111] The same results as those of Experimental Example A were obtained for the sample of Experimental Example B, which contains sodium tantalate (NaTaO3) as the base particle. That is, when the support was performed by the ultrasonic reduction method (Example B-1), the peak intensity ratio of the diffuse reflectance spectrum (I B / I A ) was 50% or less. In addition, while maintaining a CO selectivity of 80% or more, the CO gas production rate was higher than when loading was performed by another method (chemical reduction method) (Example B-2).

[0112] The same results as those of Experimental Example A were obtained for the sample of Experimental Example C, which contains zinc tantalate (ZnTa2O6) as the base particles. That is, when the support was performed by the ultrasonic reduction method (Example C-1), the peak intensity ratio of the diffuse reflectance spectrum (I B / I A ) was 50% or less. In addition, the CO gas generation rate was higher than in the cases where the catalyst was supported by other methods (chemical reduction method, impregnation method, photoelectrodeposition method) while maintaining a CO selectivity of 80% or more (Examples C-2 to C-4).

[0113] It is believed that by using the ultrasonic reduction method for loading, most of the loaded Ag particles become ultrafine clusters, and the ultrafine clustered Ag particles function as co-catalysts, thereby improving the catalytic activity.

[0114] [Table 1]

[0115] The CO2 reduction photocatalytic performance (gas generation rate and CO selectivity) obtained for the samples of Experimental Example D in which the amount of the co-catalyst (Ag particles) supported was changed from 0 to 5 mass % is shown in Table 2 below and FIG.

[0116] In the samples (Examples D-1 to D-3) in which the amount of the cocatalyst supported was more than 0 mass% and less than 1.0 mass%, the peak intensity ratio of the diffuse reflectance spectrum (I B / I A) was less than 50%. In addition, the CO gas production rate was high at more than 40%, while maintaining a CO selectivity of more than 80%.

[0117] In contrast, the sample (Example D-7) not supporting the promoter (Ag) had low CO selectivity and low CO gas production rate. Moreover, the samples (Examples D-5 to D-6) with a promoter loading of 3.0 mass% or more had low CO gas production rates.

[0118] This shows that by limiting the amount of promoter supported to more than 0 mass % and less than 1.0 mass %, photocatalyst particles with excellent catalytic activity can be obtained.

[0119] From the above results, it can be seen that the present embodiment provides carbon dioxide reduction photocatalyst particles that exhibit a high CO gas production rate while maintaining a high level of CO selectivity, and a method for producing the same.

[0120] [Table 2]

[0121] Atomic resolution TEM images were observed for Example D-3. The results are shown in Figure 15. Ag nanoparticles with particle sizes of 1 to 5 nm were observed.

[0122] The interplanar spacing of the Ag nanoparticles observed in Figure 15 was calculated to be 0.238 nm. Assuming that the Ag crystal has a face-centered cubic lattice, the interplanar spacing of the Ag(111) plane is calculated to be 0.236 nm based on the literature value of the lattice constant (0.409 nm). Therefore, the interplanar spacing calculated from the TEM image is in good agreement with the value calculated from the literature value. [Explanation of symbols]

[0123] 2. Evaluation equipment 4 tanks 6 Mercury (Hg) Lamp 8 Gas introduction pipe 10 Gas exhaust pipe 12 pH meter 14 Rubber stopper 16. Stirrer 18 Bubbling Filter 20 Cooling water 22 Evaluation solution 30 CO2 gas 32 Gas evolution 34 Gas Chromatography

Claims

1. The present invention relates to a method for producing a composite material comprising the steps of: The base particles are made of tantalum oxide (Ta 2 O 5 ), sodium tantalate (NaTaO 3 ), and zinc tantalate (ZnTa 2 O 6 ) ) ) ) ) ) ) ) ) ) In the diffuse reflectance spectrum, a peak A is located in a wavelength range of 200 nm to 300 nm, and a peak B is located in a wavelength range of 480 nm to 530 nm, and the intensity of the peak A (I A ) to the intensity of peak B (I B ) ratio (I B / I A ) is 50% or less.

2. The carbon dioxide reducing photocatalyst particles according to claim 1 , wherein the amount of the metallic silver (Ag) particles supported is greater than 0 mass % and less than 1.0 mass % with respect to the base particles.

3. 3. The carbon dioxide reducing photocatalyst particles according to claim 1 or 2, wherein the metallic silver (Ag) particles have a particle diameter of 0.1 nm to 5 nm.

4. CO 2 3. The carbon dioxide reducing photocatalyst particle according to claim 1, which has a CO selectivity of 50% or more in a reduction photoreduction catalyst performance evaluation test.

5. A method for producing carbon dioxide reducing photocatalyst particles comprising base particles and metallic silver (Ag) particles supported on the surfaces of the base particles, comprising: A step of adding base particles and a silver (Ag) source to a reduction solution to prepare a reaction solution; and The method includes a step of irradiating the reaction liquid with ultrasonic waves to prepare base particles carrying metallic silver (Ag) particles, The base particles are made of tantalum oxide (Ta 2 O 5 ), sodium tantalate (NaTaO 3 ), and zinc tantalate (ZnTa 2 O 6 The method of claim 1, further comprising:

6. The method according to claim 5 , wherein the loading of the metallic silver (Ag) particles is greater than 0 mass % and less than 1.0 mass % relative to the base particles.

Citation Information

Patent Citations

  • Method for manufacturing noble-metal nanomaterial

    JP2008024968A

  • Method of reducing carbon dioxide

    JP2012192302A